Resveratrol and radiation biological effects - Moreno, Carolina dos Santos (2022)
Resveratrol is a phytoalexin, a phenolic compound present in wines and several plants. This compound is related to a broad spectrum of biological activities such as antioxidant and anticarcinogenic effects that are very important in prevention of cancer, cardiovascular diseases and other diseases caused by oxidative processes. Over the last years, biological effects of ionizing radiation in the presence of resveratrol have been studied in different cell cultures. The aim of this study was to verify the effect of gamma radiation on mouse connective tissue cells (NCTC clone 929) in culture in the presence of trans-resveratrol. Cell viabilities were analyzed by neutral red uptake assay. The results demonstrated in vitro the radioprotective effect of trans-resveratrol on cell culture and it was more pronounced when cell culture was irradiated at 500-800 Gy doses in the presence of resveratrol concentrations between 12.5 and 25 μM. These results provide evidence that trans-resveratrol alters the cellular response to ionizing radiation, expanding the knowledge of resveratrol biological properties in physiological and pathological processes, contributing to the development of future studies about the possibility of including resveratrol and its derivatives in dietary supplements given to cancer patients during radiotherapy.